Frequency-domain analysis and design of distributed control systems - Tian, Yu-Ping.; ebrary, Inc. (Hoboken, N.J. : Wiley : IEEE Press, 2012)
"This book presents a unified frequency-domain method for the analysis of distributed control systems"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Distributed parameter systems; Time-domain analysis; Frequency curves; Electronic books